Vulval Lymphangiomas Mimicking Genital Herpes : A Need for Vigilance - Al Aboud, K (Nepal Journal of Obstetrics and Gynaecology, 2014)
DOI: http://www.dx.doi.org/10.3126/njog.v7i2.11149 Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 2 / Issue 14 / July-Dec, 2012 / 59-60